Solving the Puzzle of the September 2018 Palu, Indonesia, Tsunami Mystery: Clues from the Tsunami Waveform and the Initial Field Survey Data - Muhari, Abdul; Imamura, Fumihiko; Arikawa, Taro; Hakim, Aradea R.; Afriyanto, Bagus (Journal of disaster research, 2018)
On September 28, 2018, following a magnitude 7.5 strike-slip fault earthquake, an unexpected tsunami inundated the coast of Palu bay, Sulawesi, Indonesia, causing many casualties and extensive property damage. However, the earthquake’s mechanism rarely generates a destructive tsunami. The tidal record at Pantoloan, located along the coast of Palu bay, indicates that the tsunami arrived 6 min after the earthquake and generated 2 m of receding water. It had a maximum wave height of 2 m and arrived approximately 2 min later. The tsunami had a relatively short period and caused devastation as far inland as 300 m. Additionally, 8 m high watermarks were observed near the coast; the flow depth decreased to 3.5 m inland (Fig. 1). Amateur videos and eyewitness accounts indicate that the tsunami did not enter the bay through its mouth but obliquely from an area inside the bay. Our hypothesis, therefore, is that the killer tsunami was most likely generated by an underwater landslide occurring inside Palu bay. While detailed bathymetric data are still needed to confirm this hypothesis, in this article we provide a preliminary analysis of the available data, supported by the results of a field survey, to strengthen this hypothesis and provide direction for further post-tsunami surveys and analysis.